Should prenatal chromosomal microarray analysis be offered for isolated ventricular septal defect? A single-center retrospective study from China - Cheng, Ken; Zhou, Hang; Fu, Fang; Lei, Tingying; Li, Fucheng; Huang, Ruibin; Wang, You; Yang, Xin; Li, Ru; Li, Dongzhi; Liao, Can (Frontiers in Cardiovascular Medicine, 2022)
OBJECTIVE: To evaluate the utility of chromosomal microarray analysis (CMA) in fetuses with isolated ventricular septal defect (VSD) and to explore the favorable factors for predicting spontaneous closure of defects. METHOD: The study included 436 singleton pregnancies seen at a referral prenatal diagnosis center, between January 2016 and May 2020, of which 168 fetuses with isolated VSD were diagnosed in the prenatal setting. VSD was classified as an isolated VSD whether it had ultrasound soft markers or not. All patients underwent testing employing quantitative fluorescent polymerase chain reaction (QF-PCR) and CMA as the first-line genetic detection strategies, mainly in amniotic fluid and umbilical blood samples. Rates of chromosomal abnormalities were compared by subgroups of isolated VSD (muscular or perimembranous). Binary logistic regression analysis was performed to predict the independent determinants of spontaneous closure by two years. RESULTS: Overall, the CMA identified clinically significant copy number variations (CNVs) in 7/168 (4.2%) fetuses and variants of unknown significance (VOUS) in 15/168 (8.9%). Muscular and perimembranous VSDs were found in 53.6 and 46.4%, respectively. Clinically significant relevant subchromosomal aberrations were revealed in seven (9.0%) perimembranous VSDs compared with none in 90 muscular defects (P<0.01). The median initial size of the defect in the muscular VSDs was 2.2(1.8-2.7) mm, as compared to that of 2.8 (2.2-3.2) mm in the perimembranous VSDs group (p=0.000). In muscular vs. perimembranous VSDs, spontaneous closure occurred more frequently and earlier (40.0% vs 15.4% in utero (p=0.000), 61.1% vs 30.8% at 1-year (p=0.000), and 75.6% vs 42.3% at 2-year (P=0 .000)). Postnatal surgical closure was warranted in 4/90 (4.4%) of the infants with muscular VSDs, as compared to 29/71 (40.8%) with perimembranous defects (p=0.000). Furthermore, isolated muscular type VSD, smaller defect size, and maternal age of less than 35 years are all positive predictors of spontaneous closure of the defects. CONCLUSION: This study highlighted the value of microarray for unbalanced subchromosomal abnormalities in fetuses with isolated VSD, particularly in the perimembranous defects. The detection of an isolated muscular VSD prenatally may be considered a benign or likely benign finding; in contrast, for perimembranous VSD, a prenatal CMA should be offered.